Text of remarks... to the Annual Conference on Trade, Investment and Development in the Caribbean Basin held in Miami, Florida on 2 December 1992 - Clinton, Bill (CCS GeorgetownGY, 1993)
States the improved economic growth in the Caribbean Basin is the direct interest of the United States. Indicates that we share a common agenda of economic progress, political democracy, protecting the environment, resolving regional conflicts, strengthening and providing democracy where it does not yet exist, and eradicating drug trafficking. Supports NAFTA and continued effort to expand trade and other economic opportunities within this hemisphere.